CHOICE OF CHEMICAL COMPOSITIONS OF NEW GRADES OF TOOL STEELS WITH INCREASED WEAR RESISTANCE FOR PUNCHES OF COLD DEFORMATION - V. N. Fedulov (Литьë и металлургия)
The article is dedicated to carrying out of investigations on creation of new structures of die steels for stabilization of instrument for cold forming operation of metals and alloys.